Bridging the Gulf: Socioeconomic Disparities and the Fight for Political Inclusion in Pakistan - Fatima, Zaryab; Riaz, Nida; Asghar, Arslan (Annals of Human and Social Sciences, 2024)
This paper discusses how political participation is affected by socioeconomic differences: differences related to regions, demography, and history in the Pakistani context. The study aims to highlight major exclusion drivers through qualitative approaches: interviews and focus groups with stakeholders namely politicians, community representatives, and excluded people. Some of these barriers include political resources such as voting which is restricted, Discrimination and Power which has been placed on the side of those with higher income. The results shed the light on the need to properly address the issue of resource equality, the necessity of improving the level of people’s political awareness, and demanding activity for the implementation of the diversity policies. Therefore, the research supports the published structural deficiencies of political system in Pakistan and calls for the policy interventions.